Addressing the Effects of Size‐dependent Absorption, Scattering, and Near‐field Enhancements in Plasmonic Catalysis. Issue 16 (4th July 2018) - Geonmonond, Rafael S.; da Silva, Anderson G. M.; Rodrigues, Thenner S.; de Freitas, Isabel C.; Ando, Rômulo A.; Alves, Tiago V.; Camargo, Pedro H. C.
Abstract: Studies on surface plasmon resonance (LSPR) mediated catalytic transformations have focused on quantification of reaction rates and investigation on enhancement mechanisms. However, the establishment of structure‐performance relationships remains limited. For instance, the importance of nanoparticle size remains overlooked, and relatively large nanoparticles (>50 nm in size) are generally employed as catalysts. Herein, we unravel how plasmon decay pathways (absorption and scattering efficiencies) and electric field enhancements as a function of size dictate plasmonic catalytic performances. We employed Ag NPs having 12–50 nm in size as a proof‐of‐concept catalysts, and the LSPR‐mediated oxidation of p‐aminothiophenol to p, p′‐dimercaptoazobenzene as a model reaction. Our data and simulations revealed that the LSPR‐mediated activities displayed a volcano‐type variation with size, which was dependent on the balance among near field enhancements, absorption, and scattering. As this transformation is driven by the charge‐transfer of LSPR‐excited hot‐electrons to adsorbed O2 molecules, the variations in the optical absorption as a function of size represented the dominant contribution to the plasmonic catalytic activities. We believe our results shed important insights over the optimization of physical and chemical parameters in plasmonic nanoparticles in order to maximize plasmonic catalytic activities. Abstract : Size matters : We investigated how absorption/scattering efficiencies and the electric field enhancements due to LSPR excitation in silver nanoparticles dictate plasmonic catalytic activities as a function of size. We observed a volcano‐type relationship with size, in which the variations in the optical absorption represented the dominant contribution to the detected activities.